Economics of hypothalamic obesity in patients with craniopharyngioma and other rare sellar/suprasellar tumors - Julian Witte; Nicolas Touchot; Bastian Surmann; Mathias Flume; Julia Beckhaus; Carsten Friedrich; Hermann L. Müller (The European Journal of Health Economics, 2025)
Background: Rapid and abnormal weight gain resulting in severe persistent obesity due to physical, tumor- and/or treatment-related damage to the hypothalamus, is called acquired hypothalamic obesity (aHO), and is often linked to craniopharyngioma and/or sellar/suprasellar tumors. Here, we examine the healthcare resource use (HCRU) and costs of aHO following treatment of these tumors. Methods: We used a retrospective matched cohort design with German statutory health insurance data on 5.42~million people from 2010 to 2021. We applied a novel three-step approach using diagnostic and prescription data to identify patients with treatment- or tumor-related (TTR)-aHO. We measured HCRU and costs across hospitalizations, outpatient visits, visits per specialist group, and outpatient prescription medications. Results: Compared to non-HO obesity, TTR-aHO is associated with increased hospitalizations, increased outpatient physician visits, and increased prescription use in the two years after incident tumor surgery/radiotherapy. Excess costs of TTR-aHO are exteuro19,900 per patient in the first year and exteuro10,700 in the second, driven by inpatient costs. Cost-intensive hormone replacement therapies like somatropin lead to a sharp increase in prescription costs in the second year. Conclusions: This study provides the first real-world analysis of TTR-aHO economics, emphasizing the importance of HCRU and costs for decision-making. Previously, economic evaluations have been missing due to the lack of a standard method to identify patients with aHO in retrospective studies. Using a new identification approach, the study reveals that TTR-aHO poses a significant burden in extensive treatment requirements for patients and high related costs for the healthcare system.
Keywords: 610; Hypothalamic obesity; Tumor/treatment related aHO; Rare sellar/suprasellar tumors; Craniopharyngioma; Endocrinology